Enhancing wellbeing in medical practice: Exploring interventions and effectiveness for improving the work lives of resident (junior) doctors: A systematic review and narrative synthesis - Yuri Hirayama; Sunera Khan; Charn Gill; Maxwell Thoburn; Jennifer Hancox; Jameel Muzaffar (Future Healthcare Journal)
Introduction: Globally, resident doctors face challenges like long work hours, critical decision-making stress, and exposure to death and distress, prompting concern for their wellbeing. This study addresses the need for interventions to improve their working conditions, vital for enhancing quality of life, patient care and retaining a skilled workforce. Methods: Following PRISMA guidelines, a systematic literature review until 3 January 2024 explored interventions for resident Ddoctors pre- and post-COVID-19. It evaluated intervention effectiveness, metrics and feasibility, excluding studies with high bias risk. Results: The review identified diverse interventions, from mentoring to wellness resources, showing significant improvements in job satisfaction, mental health and professional growth among resident doctors. Due to methodological variations, a narrative synthesis was conducted. Conclusion: Effective interventions addressing resident doctors’ challenges can notably enhance their wellbeing and job satisfaction. Scaling such interventions is vital for fostering supportive work environments, sustaining the healthcare workforce and improving patient care quality.